Serum myostatin levels are associated with physical function and hospitalization in peritoneal dialysis patients - Silva, Maryanne Zilli Canedo [UNESP]; Vogt, Barbara Perez; Reis, Nayrana Soares Carmo [UNESP]; Minicucci, Fernanda Chiuso [UNESP]; Dorna, Mariana Souza [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Caramori, Jacqueline Costa Teixeira [UNESP] (Springer Nature, 2023)
Background: Myostatin functions as a negative regulator of skeletal muscle growth. The association of myostatin with muscle parameters in dialysis patients is inconsistent, and there are no studies associating myostatin with physical function and outcomes in peritoneal dialysis (PD) patients. Therefore, we assessed the association of serum myostatin with lean mass, physical function, and hospitalization in a prospective cohort of PD patients. Methods: Lean mass, physical function, and serum myostatin were assessed at baseline. Patients were followed up for at least 24 months and hospitalization was recorded. Results: Serum myostatin levels were positively correlated with handgrip strength and Appendicular Lean Mass Index among male patients. Binary logistic regression models were performed including myostatin levels and physical function parameters as independent variables. Serum myostatin, handgrip strength, gait speed, and Short Physical Performance Battery were associated with hospitalization. Conclusion: Lower serum myostatin and physical function were associated with hospitalization in PD patients.